Parasitological and haemato-biochemical response to Haemonchus contortus infection in Garole sheep - BORDOLOI, GAUTAM; JAS, RUMA; GHOSH, J D (The Indian Journal of Animal Sciences, 2012)
Garole sheep is commonly known for its lower susceptibility to parasitic diseases. Possible existence of resistance and/or resilience to Haemonchus contortus infection was explored based on the parasitological and haemato-biochemical responses in experimentally induced infection. Female Garole sheep (15) with persistently low faecal egg count (FEC) since last 1 year were selected for the experiment. Sheep were orally fed with 700 infective larvae of H. contortus (L3) per kg body weight. Prepatent periods (PP) of the infection, faecal egg count (FEC), total worm count (TWC) and selected haemato-biochemical parameters were studied. PP was found to be 16 - 17 days and FEC on 21th days postinfection (DPI) was 90Â±18.71 but after 24 DPI onwards, no egg was detected both on qualitative as well as quantitative faecal examination. Infected animals were sacrificed on 49 DPI and no worm in the abomasum and upper small intestine was detected. Haemoglobin value significantly declined from 21 DPI but PCV (packed cell volume) remained constant between infected and control groups. Total erythrocytic count (TEC) was reduced significantly in infected group between 21 to 28 DPI. Serum protein concentration including serum albumin and globulin did not change significantly due to H. contortus infection. Parasitological and haematological findings indicated that although H. contortus infection was established in Garole sheep, the parasites were eliminated at the early patent period of the infection with gradual restoration of the TEC and PCV and serum proteins concentration.